ANALISA RISIKO PADA PROYEK PEMBANGUNAN GEDUNG AUDITORIUM IAIN KOTA AMBON - Tisya Glorya Pelatta; Nelda Maelissa; Henriette Dorothy Titaley; Abraham Tuanakotta (Jurusan Teknik Sipil, 2023)
Risk management is an effort to manage risk comprehensively, planned, and structured in a good system to prevent unexpected risks. It may allow the management to expand results by identifiying and analyzing the risk to work accident in the Auditorium building project in a IAIN Ambon. Each risk in the work phase must be assessed risk professionally. The assessment method used a risk assessment matrix sourced from NHS Highland, which adopted from AS/NZS 1360:2004 Risk Management. Primary data were obtained from interviews and questionnaires. Furthermore , secondary data were collected through the company’s organizational structure and project work items. In addition, data analysis was carried out through validity and realiability test, and finally, a risk assessment was implemented. The results of this study showed that there were five risk factors; injured/stabbed by risk level of 20 work accident risk variabels, there was obvioposly one medium risk inculuded in the category high risk and 19 other variables involved in the medium risk included in the category high and 19 other variebles invoveld in the medium risk category. In consclusion,strategiees that can be carried out to prevent the risk regaarding to the classification of risk levels, namely elimination, substitution, administation, and personal protecetive Equipment (PPE).